2021
DOI: 10.3390/agronomy11030582
|View full text |Cite
|
Sign up to set email alerts
|

A Sustainable Approach for Improving Soil Properties and Reducing N2O Emissions Is Possible through Initial and Repeated Biochar Application

Abstract: Recent findings of changing climate, water scarcity, soil degradation, and greenhouse gas emissions have brought major challenges to sustainable agriculture worldwide. Biochar application to soil proves to be a suitable solution to these problems. Although the literature presents the pros and cons of biochar application, very little information is available on the impact of repeated application. In this study, we evaluate and discuss the effects of initial and reapplied biochar (both in rates of 0, 10, and 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 87 publications
0
6
1
Order By: Relevance
“…The traditional N 2 O emission pathways mainly exist in nitrification and denitrification, the substrates of which are NH 4 + -N and NO 3 − -N, respectively [32]. However, we found a negative correlation for N 2 O flux with NH 4 + -N, which is contrary to the findings of Horák et al [33], while the positive correlation for N 2 O flux with NO 3 − -N is consistent with the findings of Horák et al [33]. A reasonable explanation may be that the freeze-thaw treatment enhances the nitrification but weakens denitrification.…”
Section: Freeze-thaw Treatments Increase N 2 O Fluxcontrasting
confidence: 99%
“…The traditional N 2 O emission pathways mainly exist in nitrification and denitrification, the substrates of which are NH 4 + -N and NO 3 − -N, respectively [32]. However, we found a negative correlation for N 2 O flux with NH 4 + -N, which is contrary to the findings of Horák et al [33], while the positive correlation for N 2 O flux with NO 3 − -N is consistent with the findings of Horák et al [33]. A reasonable explanation may be that the freeze-thaw treatment enhances the nitrification but weakens denitrification.…”
Section: Freeze-thaw Treatments Increase N 2 O Fluxcontrasting
confidence: 99%
“…In accordance with our hypothesis, the alkaline soil amendments increased soil pH by 0.4–0.8 units compared to the control. Other studies in boreal and temperate regions have reported a similar liming effect with alkaline soil amendments [ 75 , 89 , 90 ] indicating that ligneous soil amendments can increase and sustain more alkaline soil pH, even though anions, such as bicarbonate, are prone to leaching. We attributed the liming effect to calcium carbonates, and to various hydroxides, oxides or silicates added to the pulp during paper production, or when the pulp sludge is sanitized [ 91 ], and to carbonates or alkaline salts (mainly oxides CaO, MgO, K 2 O) enriched during the pyrolysis processes used to produce biochar [ 92 , 93 ].…”
Section: Discussionmentioning
confidence: 64%
“…It is also possible, however, to hypothesize other reasons, mainly linked to the supply of N mineral forms (through all tested fertilizers) and labile C forms (mainly associated to animal manure, and, in particular, to digestate), which are known to boost N 2 O emissions in the short-term [46]. On the contrary, expected effects of biochar for N 2 O mitigation are often associated with improved soil aeration due to an increase in porosity, and to a shift of concentration of mineral N forms in soil [47], which could need more application in time to fully manifest the mitigation potential of biochar [48,49].…”
Section: Effect Of Biochar Introduction On N 2 O Emissions From Maizementioning
confidence: 99%